Murrays have 50th anniversary (Raton Range Raton, New Mexico, 1982)
Newspaper Article on the 50th Anniversary of Mr. and Mrs Wayne Murray.
Master list item #: 56
File location is in the Raton File Cabinet
Keywords: Murray, Wayne; Murray, (Mrs.); Murray, Donald; Murray, Anne; Revell, Lee; Revell, Judi; Murray, Dan; Revell, Lizanne; Gaussoin, Herbert; Gaussoin, (Mrs.); Doherty, Dan; Doherty, (Mrs.); Purvines, Craig; Purvines, (Mrs.); Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico